Linux Shell scripting with Bash - Burtch, Ken O. (Developer's library., 2004)
According to IDC, over 170,000 new servers were shipped in the first quarter of 2003. That also means that there were potentially more than 170,000 people like you charged with administering these systems without the proper knowledge or training to do so. Linux Shell Scripting with Bash will help you learn to not only get your system up and running quickly by employing the Bash shell, but it will also show you professional scripting solutions through the use of structured programming and standard Linux development tools. The book focuses on the Linux environment, which the shell relies on to function, and the robust Linux tool set, making this book ideal for learning shell scripting. Real-world scripts are included that are readable, extendable and easy to debug. This book is an asset to any Linux user.